1982
DOI: 10.1161/01.hyp.4.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating levels of an endogenous digoxin-like factor in hypertensive monkeys.

Abstract: SUMMARY An endogenous, immunoreactive digoxin-like factor (endoxin) was measured in the plasma of nonhuman primates with hypertension. Both normotensive and hypertensive rhesus monkeys had levels of endoxin that significantly correlated with their systolic or diastolic blood pressure. Vervet monkeys with experimentally produced chronic Goldblatt hypertension had significantly elevated endoxin, but not plasma renin. These data suggest that increased plasma endoxin may be a contributing factor in the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Recently, several reports have appeared suggesting the presence of endogenous digitalis-like substances in various organs or body fluids (5)(6)(7)(8)(9)(10)(11)(12)(13). Besides the presence of DLIS, DTLIS was detected in amniotic fluid or cord blood in our study.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, several reports have appeared suggesting the presence of endogenous digitalis-like substances in various organs or body fluids (5)(6)(7)(8)(9)(10)(11)(12)(13). Besides the presence of DLIS, DTLIS was detected in amniotic fluid or cord blood in our study.…”
Section: Discussionsupporting
confidence: 58%
“…Previous reports indicated that plasma NKI is active i) to inhibit Na, K-ATPase (Gruber et al 1980(Gruber et al , 1982.…”
Section: Discussionmentioning
confidence: 98%
“…9 Poston et al 42 have recently reported the presence of a circulating inhibitor of the ouabain sensitive 22 Na efflux of red and white cells in humans with essential hypertension. In addition, a circulating ouabain-like factor has been demonstrated in dogs with one-kidney one-wrapped hypertension, and in rats with reduced renal mass-saline hypertension.…”
Section: Discussionmentioning
confidence: 99%